Geology and Exploration Geochemistry of the Glacial Deposits of Northeastern Itasca County, Minnesota - Steinmaus, Karen (1983)
A Thesis submitted to the faculty of the Graduate School of the University of Minnesota by Karen Steinmaus in partial fulfillment of the requirements for the degree of Master of Science, September 1983. Figure 7 referenced in the thesis is also attached to this record. Late Wisconsinan glaciation produced two lobes of the Laurentide ice sheet in northeastern Minnesota: the Rainy Lobe and St. Louis Sublobe of the Des Moines Lobe. In Itasca County, deposits of the St. Louis Sublobe of the Des Moines Lobe have come in contact with, and have overridden deposits of the Rainy Lobe. The Rainy Lobe ice advanced from the northeast across the Precambrian Shield, depositing a brown sandy non-calcareous till. Deposits of the Rainy Lobe in the area are referred to as Nashwauk Drift. As the ice moved in a southwesterly direction over the crest of the Giants Range, it incorporated a large percentage of granite cobbles and boulders into its drift. Other rock fragments include metavolcanic and metasedimentary rocks of local origin, with minor basalt, gabbro and granophyre. The St. Louis Sublobe entered Minnesota from the northwest, overriding the deposits of the Rainy Lobe. St.Louis Sublobe drift, referred to as Caribou Drift, consists of a thick supraglacial accumulation of calcareous sand and gravel. The till facies is a silty, calcareous flow till containing abundant granitic and metamorphic clasts, with Paleozoic carbonate and Cretaceous shale. Groundwater, lake water and lake sediment were sampled and analyzed for Co, Cu, Ni, Zn, Fe, Mn, Ca, Mg, K, and Na, to chemically characterize the surf icial deposits. Specific conductivity, pH, and depth were also measured at each site. Multivariate statistical procedures were used to differentiate the samples, then characterize each group. Cluster analysis successfully separated the samples into two groups, which correspond to the two drift types. The dominant influence on the chemistry of the samples is the drift lithology, not climate, bedrock lithology or vegetation. Results of ...